Health Equity and Financial Protection Report : Mongolia - World Bank (Washington, DC, 2017)
The health equity and financial protection reports are short country-specific volumes that provide a picture of equity and financial protection in the health sectors of low- and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. This report analyses equity and financial protection in the health sector of Mongolia. In particular, it examines inequalities in health outcomes and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Data are drawn from the 2005 Mongolia multiple indicator cluster survey and the 2007-08 Mongolia household socio-economic survey.